The effect of exercise and physical activity-interventions on step count and intensity level in individuals with multiple sclerosis: a systematic review and meta-analysis of randomized controlled trials - Arntzen, Ellen Christin; Bidhendi-Yarandi, Razieh; Sivertsen, Marianne; Knutsen, Karina; Dahl, Stine Susanne Haakonsen; Hartvedt, Maria Grytvik; Normann, Britt; Behboudi-Gandevani, Samira (Frontiers in Sports and Active Living, 2023)
Background Reduced physical activity is a worldwide challenge in individuals with multiple sclerosis (MS). The aim of this systematic review and meta-analysis was to identify devise-measured effects of physical activity, exercise and physiotherapy-interventions on step count and intensity level of physical activity in individuals with MS. Methods A systematic search of the databases of PubMed (including Medline), Scopus, CINHAL and Web of Science was carried out to retrieve studies published in the English language from the inception to the first of May 2023. All trials concerning the effectiveness of different types of exercise on step count and intensity level in people with MS were included. The quality of the included studies and their risk of bias were critically appraised using The modified consolidated standards of reporting trials and the Cochrane Risk of Bias tool, respectively. The pooled standardized mean difference (SMD) and 95% CI of the step-count outcome and moderate to vigorous intensity level before versus after treatment were estimated in both Intervention and Control groups using the random effect model. The Harbord test were used to account for heterogeneity between studies and assess publication bias, respectively. Further sensitivity analysis helped with the verification of the reliability and stability of our review results. Results A total of 8 randomized clinical trials (involving 919 individuals with MS) were included. The participants (including 715 (77.8%) female and 204 (22.2%) male) had been randomly assigned to the Intervention (n = 493) or Control group (n = 426). The pooled mean (95% CI) age and BMI of participants were 49.4 years (95% CI: 47.4, 51.4 years) and 27.7 kg/m2 (95% CI: 26.4, 29 kg/m2), respectively. In terms of the comparison within the Intervention and the Control groups before and after the intervention, the results of the meta-analysis indicate that the pooled standardized mean difference (SMD) for step-count in the Intervention group was 0.56 (95% CI: -0.42, 1.54), while in the Control group it was 0.12 (95% CI: -0.05, 0.28). Furthermore, there was no significant difference in the pooled SMD of step-count in the physical activity Intervention group compared to the Controls after the intervention (pooled standard mean difference = 0.19, 95% CI: -0.36,0.74). Subgroup analysis on moderate to vigorous intensity level of physical activity revealed no significant effect of the physical activity intervention in the Intervention group compared to the Control group after the intervention, or within groups before and after the intervention. Results of meta regression showed that age, BMI, duration of disease and Expanded Disability Status Scale (EDSS) score were not the potential sources of heterogeneity (all p > 0.05). Data on the potential harms of the interventions were limited. Conclusion The results of this meta-analysis showed no significant differences in step count and moderate to vigorous physical activity level among individuals with MS, both within and between groups receiving physical activity interventions. More studies that objectively measure physical activity are needed. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022343621